2021
DOI: 10.1007/s42978-021-00122-4
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Vertical Jump Metrics and Sprint Performance, and Qualities that Distinguish Between Faster and Slower Sprinters

Abstract: Purpose This study aimed to investigate the relationships between vertical jump metrics and phases during a 60 m sprint. The variances in strength qualities between sprinters of different ability levels were also compared. Methods Eighteen young male elite sprinters (age: 18.1 ± 1.3 years; stature: 1.72 ± 0.07 m; body mass: 66.3 ± 6.2 kg) were assessed for squat (SJ), countermovement (CMJ), drop (DJ), and standing long jumps, a maximal load back-squat, and a 60-m sprint from a block-start. The relationships be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 28 publications
2
27
0
3
Order By: Relevance
“…In previous study, Nagahara et al and Washif et al found SJH is related to 60m sprint time (r=-0.55; r=0.65). 10,19 Other studies have reported moderate relationships between Vmax and SJ (r = 0.56 to 0.64). 5,[14][15][16][17] These data are in partial agreement with our study.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In previous study, Nagahara et al and Washif et al found SJH is related to 60m sprint time (r=-0.55; r=0.65). 10,19 Other studies have reported moderate relationships between Vmax and SJ (r = 0.56 to 0.64). 5,[14][15][16][17] These data are in partial agreement with our study.…”
Section: Discussionmentioning
confidence: 95%
“…Some research stated SJ height (SJH) and sprint acceleration performance were found to be related. 1,[10][11][12][13][14] And drop jump height (DJH) was reported by researches to have positive relationship with maximal velocity (Vmax) in sprinters. 5,14,15 Yet, other studies have reported significant relationships between Vmax and SJ.…”
Section: Introductionmentioning
confidence: 99%
“…Por outro lado, o SJmáx foi correlacionado com 60 m, mas foi maior nos 50 m, e DJ120 m foi correlacionado com 50 m. Em estudo anterior, Nagahara et al e Washif et al encontraram que a altura do SJ está relacionada com o tempo de sprint de 60 m (r = -0,55; r = 0,65). 10,19 Outros estudos relataram relações moderadas entre Vmáx e SJ (r = 0,56 a 0,64). 5,[14][15][16][17] Esses dados concordam parcialmente com nosso estudo.…”
Section: Discussionunclassified
“…6 O squat jump compreende apenas força dinâmica e explosiva com fase concêntrica e pode ser relacionado com a aceleração inicial como a parte de 5 m. Os achados atuais estão de acordo com os relatados entre desempenho de aceleração de sprint e habilidade no SJ com a faixa de correlações (r = 0,22 -0,86). 1,[10][11][12][13][14] Também foi encontrada relação significativa entre SJ e sprint de 7 a 18 m em velocistas do sexo masculino. 19 No DJ, a altura foi significativamente correlacionada com 5 m. Katja e Coh 14 relataram que altura do DJ foi correlacionada com a Vmáx da corrida de sprint de 20 m. Consequentemente, os resultados do presente estudo estão de acordo com um estudo anterior quanto à relação entre fase de aceleração e habilidade no salto bilateral.…”
Section: Discussionunclassified
See 1 more Smart Citation